Three Aeginetan odes of Pindar : a commentary on Nemean V, Nemean III and Pythian VIII - Pfeijffer, Ilja Leonard, 1968- (Mnemosyne, Supplements, 1999)
A study of three epinicia of Pindar, which have in common that they celebrate victories of Aeginetan athletes and that they respond to the contemporary political situation in Aegina and to circumstances of the victory. The primary objective of this book is to provide an interpretation of each of the three odes as meaningful, coherent works of the literary art. For each ode, it provides a commentary in which problems of text and interpretation are discussed in detail, a structural and metrical analysis, and an interpretative essay, in which the observations of detail are brought together in order to provide an answer to the question as to how the ode at hand could have functioned as a coherent, meaningful epinicion . The introduction addresses questions of method and provides a description of Pindar's style.